2017
DOI: 10.1016/j.envres.2017.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate and bisphenol A exposure during in utero windows of susceptibility in relation to reproductive hormones and pubertal development in girls

Abstract: Background Over the past several decades, the age of pubertal onset in girls has shifted downward worldwide. As early pubertal onset is associated with increased risky behavior and psychological issues during adolescence and cardiometabolic disease and cancer in adulthood, this is an important public health concern. Exposure to endocrine disrupting chemicals during critical windows of in utero development may play a role in this trend. Our objective was to investigate trimester-specific phthalate and BPA expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 86 publications
(107 reference statements)
2
68
0
Order By: Relevance
“…Zhang et al, 2020). In pregnant females, the sum of DEHP metabolites can be even higher, ranging from 78.1-93.7 μg/L (Nassan, Gunn, Hill, Williams, & Hauser, 2020;Watkins et al, 2017).…”
Section: Environmental and Clinical Exposure To Dehpmentioning
confidence: 99%
“…Zhang et al, 2020). In pregnant females, the sum of DEHP metabolites can be even higher, ranging from 78.1-93.7 μg/L (Nassan, Gunn, Hill, Williams, & Hauser, 2020;Watkins et al, 2017).…”
Section: Environmental and Clinical Exposure To Dehpmentioning
confidence: 99%
“…EDCs are widespread in the environment and can accumulate throughout the food chain, particularly since most of these lipophilic chemicals exhibit long half-lives [3]. A large body of research has indicated that in humans, prolonged exposure to these chemicals can be associated with metabolic dysfunction, disorders of the reproductive system, endocrine-related cancers, and neurodevelopmental diseases [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of BPA on neurodevelopment is not only linked to the effect on the placenta. There is also evidence of a direct effect on the fetus, such as the HPA axis, thyroid receptors, and estrogen receptors [9,[23][24][25]. Moreover, BPA exposure in utero appears to be associated with implantation problems, as well as preeclampsia, preterm births, and low birth weight [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…These trends in the timing of puberty, a period of physical and psychological development, have raised concerns regarding the potential impact of environmental factors, including endocrine disrupting chemicals (EDCs) (Blakemore et al 2010;Buck Louis et al 2008;Lee and Styne 2013;Sisk and Foster 2004). Exposure to EDCs prenatally and at the prepubertal stage are thought to play a role in altered pubertal timing, possibly via their estrogenic or anti-androgenic effects and disruption of normal homeostatic control of the hypothalamic-pituitary-gonadal (HPG) or hypothalamic-pituitary-adrenal (HPA) axis (Bellingham et al 2009;Buck Louis et al 2008;Den Hond and Schoeters 2006;Diamanti-Kandarakis et al 2009;Fudvoye et al 2019; Jacobson-Dickman and Lee 2009;Jansen et al 2018;Massart et al 2006;Parent et al 2016;Pescovitz and Walvoord 2007;Rodriguez et al 2019;Roy et al 2009;Watkins et al 2016;Watkins et al 2017).…”
Section: Introductionmentioning
confidence: 99%